Melamine-mediated POMOF-derived molybdenum carbide-loaded copper nanoparticle catalyst as well as preparation method and application thereof
By using melamine-mediated POMOF-derived POMOF-supported copper nanoparticle catalyst, selectively triggering hole degradation pathways, solving the problems of efficient removal of antibiotic pollutants and improving H2 yield in complex water quality, and achieving efficient and stable photoelectrocatalytic effects.
Patent Information
- Application Number
- CN202411787292.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The prior art is difficult to efficiently remove antibiotic pollutants from complex water quality while achieving the challenge of efficient hydrogen production, especially in terms of catalyst light absorption capacity, energy band structure and electron distribution.
The melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst is used to selectively induce hole degradation pathways to promote efficient separation of photogenerated electron-hole pairs, thereby enhancing the reduction ability of electrons to H+, realizing antibiotic degradation and improving H2 yield.
When dealing with antibiotic pollutants in complex water quality, this catalyst can efficiently remove antibiotics and produce a large amount of H2. It is strongly stable under alkaline pH conditions and is not easily affected by water quality characteristics. It is suitable for industrial production.
Smart Images

Figure CN119588398A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectrocatalytic environmental pollution control and coordinated new energy (hydrogen production), and in particular to a melamine-mediated POMOF-derived molybdenum carbide-loaded copper nanoparticle catalyst, and a preparation method and application thereof. Background Art
[0002] Water is an irreplaceable natural resource for the continuation and development of human society. The rapid development of industry has brought benefits to mankind while also bringing many pollutants that have not been effectively treated into the water environment. Among them, antibiotics from production and living processes such as agricultural medicine, breeding, animal husbandry and urban domestic sewage are important sources. Although the detection value of antibiotics in various environmental media is not high (only μg / L, ng / L or even pg / L), their chemical structure is complex and they have the characteristics of biological toxicity, environmental persistence, strong mobility and bioaccumulation. They are difficult to metabolize naturally and are often more difficult to degrade. Therefore, they will continue to accumulate, migrate and spread in the water environment, resulting in long-term pollution of the environment and potential and lasting threats to the ecological environment and human health. Given that antibiotics are already ubiquitous in the water environment and are difficult to accurately control and completely eliminate in the short term, exploring new green and efficient antibiotic deep purification technologies is an important research topic that meets the country's major strategic needs. Therefore, it is critical to develop efficient, economical, safe, stable and environmentally resistant water purification technologies.
[0003] In recent years, photoelectrocatalytic advanced oxidation technology (PEC-AOPs) that realizes the synchronous coupling of photocatalytic process (PC) and electrocatalytic process (EC) has significant advantages in removing refractory organic pollutants. On the one hand, compared with the PC process, the PEC process is a process driven by both light energy and electrical energy, which contains a bias voltage to enhance the separation of photogenerated electrons and holes, and realizes the synchronous coupling of the PC process and the EC process, which greatly improves the generation efficiency of ROS in the PC process and helps the decomposition and mineralization of pollutants. On the other hand, the PEC process not only solves the problem of difficult recovery of powdered catalysts in the PC process, but also reduces the cost of the electrolysis process driven by electricity. At the same time, in the PEC process, by using antibiotics as electron donors, H2 can be produced while degrading pollutants, which greatly improves the practicality of the PEC process and alleviates the problem of energy shortage to a certain extent. The key to achieving efficient hydrogen production while degrading pollutants is the efficient separation of photogenerated electron-hole pairs. Therefore, selectively inducing hole degradation pathways is expected to play an important role in removing antibiotic pollutants under complex water conditions and producing hydrogen efficiently, which is highly dependent on the light absorption ability, band structure and electron distribution of the catalyst.
[0004] In recent years, molybdenum carbide (Mo2C) has been studied for its advantages such as porous structure, high chemical stability, high electronic conductivity, and D orbital structure and Fermi level electronic state comparable to those of noble metals (especially Pt), which makes it have specific catalytic activity in certain chemical reactions. At the same time, the activity of Mo2C can be improved by introducing inexpensive transition metals (such as Fe, Co, Cu and Ni), which can ideally regulate the electronic state of Mo active centers. However, Mo2C obtained at high temperatures usually inevitably agglomerates, which affects its catalytic performance. To solve this problem, introducing porous carbon nitrogen materials as the supporting framework of Mo2C to reduce its aggregation and improve its conductivity is a good solution. The nitrogen-doped carbon matrix can firmly stabilize high-energy single atoms through metal-nitrogen interactions to alleviate the aggregation of metal atoms. Despite these advantages, there is still an urgent need to explore suitable precursors for the uniform hybridization of Mo and metal sources to controllably prepare optoelectronic materials with richer active sites, larger specific surface area, and larger interface to enhance visible light absorption, slow down the recombination of photogenerated electron-hole pairs, accelerate electron transfer, optimize the electron coordination environment, and reduce the reaction barrier. Summary of the invention
[0005] In view of this, the present invention aims to provide a melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst and its preparation method and application. The obtained catalyst selectively induces a single degradation pathway (hole), thereby effectively promoting the separation of photogenerated electron-hole pairs and enhancing the electron-to-H + Reduction produces H2, thereby achieving the degradation of antibiotic pollutants in complex water quality and efficient hydrogen production at the same time; the preparation method is simple, highly operational, has high antibiotic removal efficiency and excellent H2 production, a wide alkaline pH range of application, and strong electrode stability that is not easily affected by water quality characteristics, making it suitable for the treatment of difficult-to-degrade organic pollutants under complex water quality conditions, and the preparation method is simple and suitable for industrial production.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst, comprising the following steps:
[0008] (1) a methanol solution of trimesic acid, a methanol mixed solution of copper acetate monohydrate and hydrated phosphomolybdic acid, and melamine are sequentially mixed, stirred, allowed to stand, centrifuged, washed, dried, and dehydrated to obtain a POMOF / melamine catalyst precursor;
[0009] (2) The POMOF / melamine catalyst precursor is pyrolyzed to obtain a melamine-mediated POMOF-derived molybdenum carbide-loaded copper nanoparticle catalyst.
[0010] In the present invention, according to the Mott-Schottky heterojunction theory, the metal-semiconductor interface formed by the metal copper nanoparticles and Mo2C can change the electron transfer structure of Mo2C, and the rich interface between Cu, Mo2C and NC can also provide sufficient active sites. The heterostructure can also promote the separation of photogenerated electron-hole pairs to further improve the utilization efficiency of holes and electrons, thereby efficiently removing antibiotic pollutants in complex water and reducing H in water. + .
[0011] The molybdenum source of the catalyst of the present invention is polyoxometalate (POM)-hydrated phosphomolybdic acid, which usually contains metal elements in the highest valence state and has reversible multi-electron transfer capability.
[0012] The catalyst of the present invention generally utilizes the property that POM is easily dispersed in MOF to prepare a POMOF material in which POM is coated in the MOF cavity, which is conducive to uniform carbonization and avoids agglomeration.
[0013] The catalyst prepared by the present invention is mediated by melamine, which not only provides a nitrogen-carbon substrate, but also can reduce divalent copper ions into copper nanoparticles and tetravalent molybdenum into divalent molybdenum, thereby increasing the redox performance of the material.
[0014] Preferably, the concentration of the methanol solution of trimesic acid in step (1) is 2%; the concentration of the methanol mixed solution of copper acetate monohydrate and hydrated phosphomolybdic acid is 3.8-9.7%.
[0015] Preferably, in step (1), the molar ratio of trimesic acid, copper acetate monohydrate and hydrated phosphomolybdic acid is 1:1:0.2;
[0016] The mass ratio of the copper acetate monohydrate to melamine is 4:1.
[0017] Preferably, the stirring time in step (1) is 14 hours.
[0018] More preferably, in step (1), at least one of the following conditions is met:
[0019] The mixing time is 5 to 10 minutes;
[0020] The standing time is 14h;
[0021] The centrifugal speed is 8000~10000r / min;
[0022] The washing solvent was methanol;
[0023] The drying temperature is 60-80°C;
[0024] The dehydration time is 12 to 24 hours.
[0025] Preferably, in the pyrolysis step in step (2), nitrogen is used as the protective gas, the heating rate is 5-10°C / min, the pyrolysis temperature is 700-900°C, and the pyrolysis holding time is 2-3h.
[0026] In a second aspect, the present invention provides a melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst prepared by the above-mentioned preparation method.
[0027] In a third aspect, the present invention provides an anode of a photoelectrocatalytic reactor, which is prepared by a drop coating method using the above-mentioned melamine-mediated POMOF-derived molybdenum carbide-loaded copper nanoparticle catalyst.
[0028] In a fourth aspect, the present invention provides the use of the above-mentioned melamine-mediated POMOF-derived molybdenum carbide-loaded copper nanoparticle catalyst in the photoelectrocatalytic removal of antibiotics from wastewater while producing H2, wherein the antibiotics include one or more of tetracycline, chloramphenicol, doxycycline, and ciprofloxacin.
[0029] Preferably, the photoelectrocatalytic reactor is an H-type dual-chamber reactor, wherein the anode is the anode prepared above and the cathode is a platinum sheet electrode.
[0030] Preferably, the H-type dual-chamber reactor is separated by a DuPont Nafion proton membrane.
[0031] Preferably, the anode electrolyte solution in the H-type dual-chamber reactor is a 0.1 mol / L sodium sulfate solution, and the cathode electrolyte is a 1.0 mol / L potassium hydroxide solution.
[0032] The pH value of the reaction system for removing antibiotics from wastewater is 3-11, the temperature of the reaction system is 25-30°C, the voltage is 0.5-3.5V, and the light intensity is 2.4W / cm 2 .
[0033] Preferably, the quencher for removing antibiotics from wastewater includes disodium ethylenediaminetetraacetic acid, tert-butyl alcohol, furfuryl alcohol and nitro blue tetrazolium.
[0034] Beneficial technical effects:
[0035] (1) Based on the Mott-Schottky heterojunction theory, the present invention constructs a metal-semiconductor interface formed by combining metal copper nanoparticles and Mo2C, which not only provides sufficient active sites, but also promotes the separation of photogenerated electron-hole pairs to further improve the utilization efficiency of holes and electrons, thereby efficiently removing antibiotic pollutants in complex water and reducing H in water. + Produces H2;
[0036] The catalyst prepared by the present invention is derived from POMOF, inherits the adjustable morphology and multifunctionality of POMOF, thereby being able to expose more active sites; meanwhile, it has good dispersibility, overcoming the problem of easy agglomeration of Mo2C.
[0037] (2) The catalyst is prepared by a one-step calcination method, and the synthesis process is simple. The catalyst raw materials use copper acetate monohydrate as the metal source and H3BTC as the ligand, which has the advantages of wide material sources and low cost.
[0038] (3) The present invention physically separates the anode degradation chamber from the cathode reduction chamber, thereby achieving the degradation of the anode antibiotic and the cathode H + The reduction of H is carried out simultaneously and efficiently, and by preparing a catalyst that can selectively induce a single degradation pathway (hole), it effectively promotes the separation of photogenerated electron-hole pairs and enhances the electron-to-H + Reduction to produce hydrogen, with a reaction time of 10 to 15 minutes, can achieve greater than 90% antibiotic removal and 204.3 μmol H2 production. It is not easily affected by water quality characteristics and has a wide alkaline pH range of application. It has broad application prospects in treating antibiotic pollutants in complex water and producing hydrogen at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0040] Figure 1 The removal rate diagram of DOX degradation by the catalysts prepared in Examples 1 to 5 in the photoelectrocatalytic system;
[0041] Figure 2 Graph showing cathode H2 production of the catalysts prepared in Examples 1 to 5 in the photoelectrocatalytic degradation system of DOX;
[0042] Figure 3 The figure is a graph showing the removal rate of the catalysts prepared in Examples 2 and Examples 6 to 8 for anode-degraded DOX in a photoelectrocatalytic system;
[0043] Figure 4 It is a cathode H2 production diagram of the catalysts prepared in Examples 2 and Examples 6 to 8 in the photoelectrocatalytic degradation of DOX system;
[0044] Figure 5It is a graph showing the removal rate of DOX by anode degradation in a photoelectrocatalytic system using the catalysts prepared in Examples 1 and Examples 9 to 11;
[0045] Figure 6 The cathode H2 production of the catalysts prepared in Examples 1 and 9 to 11 in the photoelectrocatalytic degradation system of DOX;
[0046] Figure 7 The removal rate diagram of the catalysts prepared in Example 1 and Examples 12-13 for anode degradation of DOX in a photoelectrocatalytic system;
[0047] Figure 8 It is a cathode H2 production diagram of the catalysts prepared in Examples 1 and Examples 12-13 in the photoelectrocatalytic degradation system of DOX;
[0048] Fig. 9 is a scanning electron microscope image of the uncalcined catalyst prepared in Example 5;
[0049] Fig.10 is a scanning electron microscope image of the uncalcined catalyst prepared in Example 2;
[0050] Fig.11 is a scanning electron microscope image of the uncalcined catalyst prepared in Example 1;
[0051] Fig.12 is a scanning electron microscope image of the catalyst prepared in Example 1;
[0052] Fig.13 X-ray diffraction patterns of the catalysts prepared in Example 1, Example 2, Example 5 and the uncalcined Example 5;
[0053] Fig.14 Graph showing the effect of different external voltages on the anodic degradation of DOX by the catalyst prepared in Example 1 in the photoelectrocatalytic system;
[0054] Fig.15 The effect of different external voltages on the cathode H2 production of the catalyst prepared in Example 1 in the photoelectrocatalytic degradation system of DOX;
[0055] Fig.16 The effect of different initial pH on the anodic degradation of DOX by the catalyst prepared in Example 1 in the photoelectrocatalytic system;
[0056] Fig.17 The effect of different initial pH on the cathode H2 production of the catalyst prepared in Example 1 in the photoelectrocatalytic degradation of DOX system;
[0057] Fig.18The anodic degradation diagram of different pollutants by the catalyst prepared in Example 1 in the photoelectrocatalytic system;
[0058] Fig.19 This is a graph of cathode H2 production when the catalyst prepared in Example 1 degrades different pollutants in a photoelectrocatalytic system;
[0059] Fig. 20 The removal rate of DOX degraded at the anode in the photoelectrocatalytic system after the catalyst prepared in Example 1 was recycled 4 times and re-fired;
[0060] Fig.21 The cathode H2 production diagram of the catalyst prepared in Example 1 in the photoelectrocatalytic degradation system after 4 cycles and re-firing;
[0061] Fig. 22 This is a quenching experiment diagram of the catalyst prepared in Example 1 in the photoelectrocatalytic degradation system of DOX;
[0062] Fig.23 This is a graph of cathode H2 production when the catalyst prepared in Example 1 is quenched in the photoelectrocatalytic degradation DOX system. DETAILED DESCRIPTION
[0063] The present invention will be described in detail below by specific examples. These examples are provided in order to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. The test methods in the following examples, unless otherwise specified, are conventional methods. Unless otherwise specified, the reagents and materials used can all be obtained through commercial channels.
[0064] Example 1
[0065] This embodiment provides a melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst, and the preparation steps are as follows:
[0066] 1) Under magnetic stirring, H3BTC (0.62 g, 3.0 mmol) was dissolved in methanol solution (40 ml) to form solution A, copper acetate monohydrate (0.6 g, 3.0 mmol) and hydrated phosphomolybdic acid (1.24 g, 0.6 mmol) were dissolved in methanol solution (40 ml) to form solution B, then solution A was slowly added to solution B and 0.15 g of melamine was added and stirred at room temperature for 14 h to obtain a blue-green precipitate, which was washed twice with methanol and distilled water respectively, collected by centrifugation and dried overnight at 60 ° C to obtain a POMOF / melamine catalyst.
[0067] 2) The POMOF / melamine catalyst was placed in a quartz boat and then transferred to a tubular furnace. Nitrogen was introduced into the tubular furnace to expel the air. Then, the temperature was increased to 800°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2 hours for pyrolysis. After cooling to room temperature, the melamine-mediated POMOF-derived Cu / Mo2C / NC-5-0.25-800 catalyst was obtained.
[0068] Example 2
[0069] The preparation method of this embodiment is the same as that of embodiment 1, except that melamine is not added to obtain Cu / MoO2-5-800.
[0070] Example 3
[0071] The preparation method of this embodiment is the same as that of embodiment 1, except that copper acetate monohydrate and H3BTC are not added to obtain Mo2C / NC-0.25-800.
[0072] Example 4
[0073] The preparation method of this embodiment is the same as that of embodiment 1, except that hydrated phosphomolybdic acid is not added to obtain Cu / Cu2O / NC-0.25-800.
[0074] Example 5
[0075] The preparation method of this embodiment is the same as that of embodiment 1, except that hydrated phosphomolybdic acid and melamine are not added to obtain Cu / Cu2O-800.
[0076] Experimental Example 1
[0077] The removal rate of DOX in water and the H2 production of the products of Examples 1 to 5 were tested, and the testing method was as follows:
[0078] An H-type dual-chamber reactor with a single-chamber effective volume of 100 ml was selected as the photoelectrocatalytic reactor, and the catalyst prepared in Examples 1 to 5 above was used as the FTO working electrode prepared by the drop coating method as the anode (effective area of 1×2 cm 2 ), the foil is used as cathode (effective area is 1×2cm 2 ) constructed a PEC reactor, the anode chamber and cathode chamber of the reactor were separated by a N117 proton membrane with a diameter of 30 mm, the electrolyte solution in the anode solution was a 0.1 mol / L Na2SO4 solution, the electrolyte solution in the cathode solution was a 1.0 mol / L KOH solution, and the anode light source was a 250 W xenon lamp with an ultraviolet filter (λ>420 nm); 100 mL of simulated organic wastewater with an initial DOX concentration of 10 mg / L was configured, the DC power supply voltage was 2.5 V, and the light intensity was 2.4 W / cm 2Without adjusting the wastewater pH (the wastewater pH was 6.54 at this time), the reaction was carried out at 25°C with sufficient stirring by a magnetic stirrer. The residual concentration of DOX at the anode and the H2 production at the cathode were measured at 1 min, 3 min, 5 min, 7 min, 10 min and 15 min of reaction, and the removal rate of DOX and the amount of hydrogen produced were calculated.
[0079] The calculation results are as follows Figure 1 and Figure 2 As shown in the figure, the degradation performance of Cu / MoO2 derived by adding POM is enhanced compared with Cu / Cu2O derived from Cu-MOF alone, and its hydrogen production is also improved, but the effect is not significant; in addition, the degradation performance of Cu / MoC2 / NC generated by adding melamine is further enhanced, and the hydrogen production is as high as 204.3 μmol. However, by studying the Cu / Cu2O / NC and MoC2 / NC derived by adding melamine to MOF and POM materials alone, it is found that the addition of melamine inhibits their degradation and hydrogen production performance, which indicates that the Mott-Schottky heterojunction composed of copper nanoparticles and molybdenum carbide is the dominant factor for its excellent performance. The metal-semiconductor interface formed by the combination of metal copper nanoparticles and Mo2C not only provides sufficient active sites, but also promotes the separation of photogenerated electron-hole pairs to further improve the utilization efficiency of holes and electrons, thereby reducing H in water while efficiently removing antibiotic pollutants in complex water. + Produces H2.
[0080] Example 6
[0081] The preparation method of this embodiment is the same as that of Example 1, except that 3.0 mmol of copper acetate monohydrate (0.6 g) and 0.3 mmol of hydrated phosphomolybdic acid (0.62 g) are added to solution B, and no melamine is added to the solution after mixing, thereby obtaining Cu / Mo2O-10-800.
[0082] Example 7
[0083] The preparation method of this embodiment is the same as that of Example 1, except that 3.0 mmol of copper acetate monohydrate (0.6 g) and 0.9 mmol of hydrated phosphomolybdic acid (1.86 g) are added to solution B, and no melamine is added to the solution after mixing, thereby obtaining Cu / Mo2O-3.3-800.
[0084] Example 8
[0085] The preparation method of this embodiment is the same as that of Example 1, except that 3.0 mmol of copper acetate monohydrate (0.6 g) and 1.2 mmol of hydrated phosphomolybdic acid (2.48 g) are added to solution B, and no melamine is added to the solution after mixing, thereby obtaining Cu / Mo2O-2.5-800.
[0086] Example 9
[0087] The preparation method of this embodiment is the same as that of embodiment 1, except that the amount of melamine added is 0.6 g, and Cu / Mo2C / NC-5-1.0-800 is obtained.
[0088] Example 10
[0089] The preparation method of this embodiment is the same as that of embodiment 1, except that the amount of melamine added is 0.3 g, and Cu / Mo2C / NC-5-0.5-800 is obtained.
[0090] Embodiment 11
[0091] The preparation method of this embodiment is the same as that of embodiment 1, except that the amount of melamine added is 0.075 g, and Cu / Mo2C / NC-5-0.125-800 is obtained.
[0092] Experimental Example 2
[0093] The removal rate of DOX in water and the H2 production of the products of Example 1 and Examples 6 to 11 were tested, and the testing method was as follows:
[0094] An H-type dual-chamber reactor with a single-chamber effective volume of 100 ml was selected as the photoelectrocatalytic reactor, and the catalysts prepared in Examples 1 and 6 to 11 were prepared by drop coating on an FTO working electrode as the anode (effective area of 1×2 cm 2 ), the foil is used as cathode (effective area is 1×2cm 2 ) constructed a PEC reactor, the anode chamber and cathode chamber of the reactor were separated by a N117 proton membrane with a diameter of 30 mm, the electrolyte solution in the anode solution was a 0.1 mol / L Na2SO4 solution, the electrolyte solution in the cathode solution was a 1.0 mol / L KOH solution, and the anode light source was a 250 W xenon lamp with an ultraviolet filter (λ>420 nm); 100 mL of simulated organic wastewater with an initial DOX concentration of 10 mg / L was configured, the DC power supply voltage was 2.5 V, and the light intensity was 2.4 W / cm 2 Without adjusting the wastewater pH (the wastewater pH was 6.54 at this time), the reaction was carried out at 25°C with sufficient stirring by a magnetic stirrer. The residual concentration of DOX at the anode and the H2 production at the cathode were measured at 1 min, 3 min, 5 min, 7 min, 10 min, and 15 min of the reaction, and the removal rate of DOX and the amount of hydrogen produced were calculated.
[0095] The calculation results are as follows Figure 3-6 As shown, the optimal molar ratio of copper to molybdenum is 1:5, and the optimal addition amount of melamine compared to copper acetate is 25% (0.25).
[0096] Example 12
[0097] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of the tube furnace is raised to 700° C. to obtain Cu / Mo2C / NC-5-0.25-700.
[0098] Embodiment 13
[0099] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of the tube furnace is raised to 900° C. to obtain Cu / Mo2C / NC-5-0.25-900.
[0100] Experimental Example 3
[0101] The removal rate of DOX and H2 production in water by the products of Example 1 and Examples 12 to 13 were tested, and the testing method was as follows:
[0102] An H-type dual-chamber reactor with a single-chamber effective volume of 100 ml was selected as the photoelectrocatalytic reactor, and the FTO working electrode prepared by the drop coating method using the catalyst prepared in the above Example 1 and Examples 12 to 13 was used as the anode (effective area of 1×2 cm 2 ), the foil is used as cathode (effective area is 1×2cm 2 ) constructed a PEC reactor, the anode chamber and cathode chamber of the reactor were separated by a N117 proton membrane with a diameter of 30 mm, the electrolyte solution in the anode solution was a 0.1 mol / L Na2SO4 solution, the electrolyte solution in the cathode solution was a 1.0 mol / L KOH solution, and the anode light source was a 250 W xenon lamp with an ultraviolet filter (λ>420 nm); 100 mL of simulated organic wastewater with an initial DOX concentration of 10 mg / L was configured, the DC power supply voltage was 2.5 V, and the light intensity was 2.4 W / cm 2 Without adjusting the wastewater pH (the wastewater pH was 6.54 at this time), the reaction was carried out at 25°C with sufficient stirring by a magnetic stirrer. The residual concentration of DOX at the anode and the H2 production at the cathode were measured at 1 min, 3 min, 5 min, 7 min, 10 min, and 15 min of the reaction, and the removal rate of DOX and the amount of hydrogen produced were calculated.
[0103] The calculation results are as follows Figure 7 and Figure 8 As shown, the optimal calcination temperature is 800℃.
[0104] Figure 9-12 The scanning electron microscope images of the catalysts prepared in Example 1, Example 2 and Example 5 without calcination. Figure 9-11It can be seen that the catalyst of Example 5 has an obvious octahedral structure before calcination. After adding phosphomolybdic acid, it still maintains the octahedral shape, but its surface is smoother and the crystal structure of the catalyst is more obvious. However, after adding melamine, no octahedral structure is formed, which indicates that the addition of melamine will destroy the formation of its structure. Fig.12 It can be seen that the surface of the catalyst in Example 1 is rougher, and the catalyst after calcination is in a cluster structure. The X-ray diffraction patterns of the catalysts prepared in Example 1, Example 2, Example 5 and Example 5 without calcination are shown in FIG. Fig.13 . As shown in the figure, the uncalcined catalyst prepared in Example 5 exhibits obvious characteristic peaks at 2θ=6.5°, 9.5°, 11.5°, 13.4°, 19.3° and 26°, confirming the formation of its crystalline phase. The intensity variation of different diffraction peaks can be attributed to the degree of hydration of different samples. In addition, the catalysts of Example 1, Example 2 and Example 5 exhibit obvious characteristic peaks at 2θ=43.4°, 50.6° and 74.3°, confirming the presence of Cu nanoparticles, the catalyst of Example 2 confirms the presence of MoO2 at 2θ=36.5° and 53.3°, and the catalyst of Example 1 confirms the presence of Mo2C at 2θ=34.3° and 39.4°.
[0105] Embodiment 14
[0106] This embodiment provides a melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst, and the preparation steps are as follows:
[0107] 1) Under magnetic stirring, H3BTC (0.62 g, 3.0 mmol) was dissolved in methanol solution (40 ml) to form solution A, copper acetate monohydrate (0.6 g, 3.0 mmol) and hydrated phosphomolybdic acid (1.24 g, 0.6 mmol) were dissolved in methanol solution (40 ml) to form solution B, then solution A was slowly added to solution B and 0.15 g of melamine was added and stirred at room temperature for 14 h to obtain a blue-green precipitate, which was washed twice with methanol and distilled water respectively, collected by centrifugation and dried overnight at 60 ° C to obtain a POMOF / melamine catalyst.
[0108] 2) The POMOF / melamine catalyst was placed in a quartz boat and then transferred to a tubular furnace. Nitrogen was introduced into the tubular furnace to expel the air. Then, the temperature was increased to 800°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2 hours for pyrolysis. After cooling to room temperature, the melamine-mediated POMOF-derived Cu / Mo2C / NC-5-0.25-800 catalyst was obtained.
[0109] Experimental Example 4
[0110] Four treatment groups were set up with the catalyst prepared in Example 14: an H-type double-chamber reactor with a single chamber effective volume of 100 ml was selected as the photoelectrocatalytic reactor, and the FTO working electrode prepared by the drop coating method using the catalyst prepared in Example 1 and Examples 12 to 13 was used as the anode (effective area of 1×2 cm 2 ), the foil is used as cathode (effective area is 1×2cm 2 ) was used to construct a PEC reactor. The anode chamber and cathode chamber of the reactor were separated by a N117 proton membrane with a diameter of 30 mm. The electrolyte solution in the anode solution was a 0.1 mol / L Na2SO4 solution, the electrolyte solution in the cathode solution was a 1.0 mol / L KOH solution, and the anode light source was a 250 W xenon lamp with an ultraviolet filter (λ>420 nm). 100 mL of simulated organic wastewater with an initial DOX concentration of 10 mg / L was prepared. The DC power supply voltages were 0.5 V (treatment group 1), 1.5 V (treatment group 2), 2.5 V (treatment group 3), and 3.5 V (treatment group 4), respectively. The light intensity was 2.4 W / cm 2 Without adjusting the wastewater pH (the wastewater pH was 6.54 at this time), the reaction was carried out at 25°C with sufficient stirring by a magnetic stirrer. The residual concentration of DOX at the anode and the H2 production at the cathode were measured at 1 min, 3 min, 5 min, 7 min, 10 min, and 15 min of the reaction, and the removal rate of DOX and the amount of hydrogen produced were calculated.
[0111] The calculation results are as follows Fig.14 and 15 As shown in the figure, the optimal external voltage is 2.5V. If the voltage is too low, the photogenerated electrons cannot be transferred to the cathode, resulting in the recombination of photogenerated electron-hole pairs, reducing its degradation rate and hydrogen production. If the voltage is too high, it will tend to electrolyze water, competing with the degradation of DOX and thus reducing its degradation efficiency.
[0112] Experimental Example 5
[0113] Six treatment groups were set up with the catalyst prepared in Example 1: an H-type double-chamber reactor with a single chamber effective volume of 100 ml was selected as the photoelectrocatalytic reactor, and the FTO working electrode prepared by the drop coating method using the catalyst prepared in Example 1 and Examples 12 to 13 was used as the anode (effective area of 1×2 cm 2 ), the foil is used as cathode (effective area is 1×2cm 2) constructed a PEC reactor, the anode chamber and cathode chamber of the reactor were separated by a N117 proton membrane with a diameter of 30 mm, the electrolyte solution in the anode solution was a 0.1 mol / L Na2SO4 solution, the electrolyte solution in the cathode solution was a 1.0 mol / L KOH solution, and the anode light source was a 250 W xenon lamp with an ultraviolet filter (λ>420 nm); 100 mL of simulated organic wastewater with an initial DOX concentration of 10 mg / L was configured, the DC power supply voltage was 2.5 V, and the light intensity was 2.4 W / cm 2 The initial pH of the sewage was adjusted to 3 (treatment group 1), 5 (treatment group 2), 7 (treatment group 3), 9 (treatment group 4), 11 (treatment group 5), and raw water (treatment group 6), and the reaction was carried out by fully stirring with a magnetic stirrer at 25°C. The residual concentration of DOX at the anode and the H2 production at the cathode were measured at 1 min, 3 min, 5 min, 7 min, 10 min, and 15 min of the reaction, and the removal rate of DOX and the hydrogen production were calculated.
[0114] The calculation results are as follows Fig.16 and Fig.17 As shown, its optimal pH treatment range is 5-11, indicating that it has significant pH adaptability in alkaline water bodies.
[0115] Experimental Example 6
[0116] Four treatment groups were set up with the catalyst prepared in Example 1: an H-type double-chamber reactor with a single chamber effective volume of 100 ml was selected as the photoelectrocatalytic reactor, and the FTO working electrode prepared by the drop coating method using the catalyst prepared in Example 1 and Examples 12 to 13 was used as the anode (effective area of 1×2 cm 2 ), the foil is used as cathode (effective area is 1×2cm 2 ) was used to construct a PEC reactor. The anode chamber and cathode chamber of the reactor were separated by a N117 proton membrane with a diameter of 30 mm. The electrolyte solution in the anode solution was a 0.1 mol / L Na2SO4 solution, the electrolyte solution in the cathode solution was a 1.0 mol / L KOH solution, and the anode light source was a 250 W xenon lamp with an ultraviolet filter (λ>420 nm). 100 mL of simulated organic wastewater containing different pollutants with an initial concentration of 10 mg / L was prepared: tetracycline (treatment group 1), chlortetracycline (treatment group 2), doxycycline (treatment group 3), and ciprofloxacin (treatment group 4). The DC power supply voltage was 2.5 V and the light intensity was 2.4 W / cm 2Without adjusting the wastewater pH (the wastewater pH was 6.54 at this time), the reaction was carried out at 25°C with sufficient stirring by a magnetic stirrer. The residual concentration of anode pollutants and the cathode H2 production were measured at 1 min, 3 min, 5 min, 7 min, 10 min, and 15 min of reaction, and the removal rate of pollutants and the amount of hydrogen produced were calculated.
[0117] The calculation results are as follows Figure 18-19 As shown, it shows that it has a certain removal ability and hydrogen production ability for tetracycline antibiotics.
[0118] Experimental Example 7
[0119] The catalyst prepared in Example 1 was used to test the cyclic stability of the catalyst: an H-type dual-chamber reactor with a single chamber effective volume of 100 ml was selected as the photoelectrocatalytic reactor, and the catalysts prepared in Example 1 and Examples 12 to 13 were used as the anode (with an effective area of 1×2 cm 2 ), the foil is used as cathode (effective area is 1×2cm 2 ) constructed a PEC reactor, the anode chamber and cathode chamber of the reactor were separated by a N117 proton membrane with a diameter of 30 mm, the electrolyte solution in the anode solution was a 0.1 mol / L Na2SO4 solution, the electrolyte solution in the cathode solution was a 1.0 mol / L KOH solution, and the anode light source was a 250 W xenon lamp with an ultraviolet filter (λ>420 nm); 100 mL of simulated organic wastewater with an initial DOX concentration of 10 mg / L was configured, the DC power supply voltage was 2.5 V, and the light intensity was 2.4 W / cm 2 Without adjusting the wastewater pH (the wastewater pH is 6.54 at this time), the reaction was fully stirred by a magnetic stirrer at 25°C, and the residual concentration of DOX at the anode and the H2 production at the cathode were measured at 1min, 3min, 5min, 7min, 10min, and 15min of reaction, and the removal rate of DOX and the amount of hydrogen produced were calculated. After the reaction was completed, the anode working electrode was washed with deionized water, filtered and dried, and a cycle experiment was carried out according to the above test method.
[0120] Test results such as Figure 20-21 As shown, it shows that it has significant stability within 4 cycles and can recover certain performance after re-firing.
[0121] Experimental Example 8
[0122] Four treatment groups and one untreated group were set up with the catalysts prepared in Examples 1 to 5 for quenching experiments: an H-type double-chamber reactor with a single chamber effective volume of 100 ml was selected as the photoelectrocatalytic reactor, and the catalysts prepared in Examples 1 and 12 to 13 were used as the anode (with an effective area of 1×2 cm 2 ), the foil is used as cathode (effective area is 1×2cm 2 ) constructed a PEC reactor, the anode chamber and cathode chamber of the reactor were separated by a N117 proton membrane with a diameter of 30 mm, the electrolyte solution in the anode solution was a 0.1 mol / L Na2SO4 solution, the electrolyte solution in the cathode solution was a 1.0 mol / L KOH solution, and the anode light source was a 250 W xenon lamp with an ultraviolet filter (λ>420 nm); 100 mL of simulated organic wastewater with an initial DOX concentration of 10 mg / L was configured, the DC power supply voltage was 2.5 V, and the light intensity was 2.4 W / cm 2 Without adjusting the wastewater pH (the wastewater pH was 6.54 at this time), 500mmol / L tert-butyl alcohol (TBA) was added as a quencher of hydroxyl radicals (treatment group 1), 10mmol / L disodium ethylenediaminetetraacetic acid (EDTA-2Na) was added as a quencher of holes (treatment group 2), 10mmol / L furfuryl alcohol (FFA) was added as a quencher of singlet oxygen (treatment group 3), and 10mmol / L nitro blue tetrazolium (NBT) was added as a quencher of superoxide radicals (treatment group 4). The mixture was stirred thoroughly with a magnetic stirrer at 25°C for reaction. The residual concentration of DOX at the anode and the H2 production at the cathode were measured at 1min, 3min, 5min, 7min, 10min, and 15min of the reaction, and the removal rate of DOX and the hydrogen production were calculated.
[0123] The calculation results are as follows Figure 22-23 As shown, it is a hole-dominated reaction.
[0124] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst, characterized in that: The following steps are involved: (1) a methanol solution of trimesic acid, a methanol mixed solution of copper acetate monohydrate and hydrated phosphomolybdic acid, and melamine are sequentially mixed, stirred, allowed to stand, centrifuged, washed, dried, and dehydrated to obtain a POMOF / melamine catalyst precursor; (2) The POMOF / melamine catalyst precursor is pyrolyzed to obtain a melamine-mediated POMOF-derived molybdenum carbide-loaded copper nanoparticle catalyst.
2. The preparation method according to claim 1, characterized in that: The concentration of the methanol solution of trimesic acid in the step (1) is 2%; the concentration of the methanol mixed solution of copper acetate monohydrate and hydrated phosphomolybdic acid is 3.8-9.7%.
3. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of trimesic acid, cupric acetate monohydrate and hydrated phosphomolybdic acid is 1:1:0.2; The mass ratio of the copper acetate monohydrate to melamine is 4:
1.
4. The preparation method according to claim 1, characterized in that: The stirring time in step (1) is 14 hours.
5. The method according to claim 1, characterized in that In the pyrolysis step in step (2), nitrogen is used as the protective gas, the heating rate is 5-10° C. / min, the pyrolysis temperature is 700-900° C., and the pyrolysis holding time is 2-3 h.
6. A melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 5.
7. An anode of a photoelectrocatalytic reactor, characterized in that: The melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst according to claim 6 is prepared by a drop coating method; the loading amount of the catalyst is 5 mg / cm 2 .
8. The use of the melamine-mediated POMOF-derived molybdenum carbide-supported copper nanoparticle catalyst according to claim 6 in photoelectrocatalytic removal of antibiotics from wastewater while producing H2, characterized in that: The antibiotics include one or more of tetracycline, chlortetracycline, doxycycline, and ciprofloxacin.
9. The use according to claim 8, characterized in that: The photoelectrocatalytic reactor is an H-type double-chamber reactor, wherein the anode is the anode prepared according to claim 7, and the cathode is a platinum sheet electrode.
10. The use according to claim 8, characterized in that: The anolyte solution in the H-type double-chamber reactor is a 0.1 mol / L sodium sulfate solution, and the cathode electrolyte is a 1.0 mol / L potassium hydroxide solution; The pH value of the reaction system for removing antibiotics from wastewater is 3-11, the temperature of the reaction system is 25-30°C, the voltage is 0.5-3.5V, and the light intensity is 2.4W / cm 2 .
Citation Information
Patent Citations
Phosphorus-doped carbon-loaded molybdenum-tungsten carbide catalyst, preparation and application thereof
CN111215104A
Water electrolysis hydrogen evolution catalyst and preparation and application thereof
CN114045527A
Carbide-loaded noble metal monatomic catalyst and preparation and application thereof
CN114522706A
Method for producing a composite metal-dispersed coating, dispersed system for precipitation of composite metal-dispersed coating and method of its production
RU2746861C1
Photoelectrochemical production of hydrogen from wastewater
US20240352597A1